Analisis Laporan Keuangan Untuk Menilai Kinerja Keuangan pada PT Bank Mandiri Tbk yang Terdaftar di Bursa Efek Indonesia - Rizki Adriani; Miftha Rizkina; Nina Andriany Nasution (Cattleya Darmaya Fortuna, 2026)
Bank performance is an important aspect for various stakeholders as it serves as a basis for decision making. This study aims to analyze financial statements to assess the financial performance of PT Bank Mandiri Tbk, listed on the Indonesia Stock Exchange. The research method used is descriptive quantitative, utilizing the financial statements of PT Bank Mandiri Tbk for the period 2019-2023, accessed through the official website of the Indonesia Stock Exchange. Bank Mandiri's liquidity over the past five years has remained unstable. Although it temporarily recovered in 2022, this ratio declined again in 2023. The solvency ratio shows a positive recovery trend after the pandemic. This is marked by a consistent decline in the Debt to Equity Ratio (DER). In terms of activity ratios, there has been a positive recovery trend post-pandemic. This is indicated by a consistent decrease in the Debt to Equity Ratio (DER). Bank Mandiri has recorded positive and consistent growth in ROA, ROE, and NPM after the pandemic period. This increase reflects effective asset management, appropriate business strategies, and improving operational efficiency.